Strategy Proposal for Pelita Rakyat Hospital as Non Profit Organization in Sukabumi - Simanjuntak, Yosua Arthur Burhandito; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2013)
The Hospital is an institution which provides health service for people with their own characteristic. It influenced by the development of health science, technological advances, and economic-social living of society. As institution, they need to fund their activites. It could be come from government subsidies or fee charge from patient. Pelita Rakyat hospital is non-profit hospital which established in 2011. As pioneer, they did not ask charge from their patient moreover they provide free medical service include drug for all people in Sukabumi. Since 2011, Pelita Rakyat hospital has been facing a problem in Hospital facility. Hospital facility is become a concern because Pelita Rakyat infrastructure such as laboratory and medical waste system are needed to be establish as well as visiting schedule for doctor. All the weakness becomes reasonable because this hospital is running less than two years from July 2011. Most of their financing comes from donors and grants but they do that strategy without long term planning. As a new non-profit organization, the management hasn’t had long term planning strategy yet especially in financial planning. This condition will be an obstacle to meet the requirement of hospital facilities and this is basic question for Pelita Rakyat to formulate several strategies regarding that problem.This research will use qualitative method which its data are come from the interview as primary data and books, articles and journals as secondary data. The interview has objective to get new data and confirm the respondent about his idea. In business exploration, this article will analyze and propose strategy for hospital as non-profit organization. In the first time, we should do internal (Value Chain Analysis) and external (PEST and Porter forces) factor scanning that relate to hospital and list it as Strength, Weaknesses, Opportunity and Threats (SWOT). From Analyzing rating of factors through IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary), it is concluded that Pelita Rakyat hospital have less strength and more opportunities (locate in Quadrant II, horizontal integration). As a result, Pelita Rakyat hospital should implement competitive strategy through differentiation focus will give Pelita Rakyat hospital full attention to improve medical facilities for low-class income while strategic alliances with other institution will enhance hospitals support in financial or human resources. As non profit organization, to fund hospital activites, Pelita Rakyat hospital must do fundraising program: charity night, deploying volunteer. Keyword: hospital, non-profit organization, hospital facility, strategy